Geological Considerations Related to Casing setting depth selection and design of Iraqi oil wells (case study) - Assi, Amel (Iraqi Journal of Chemical and Petroleum Engineering, 2022)
Well integrity is a vital feature that should be upheld into the lifespan of the well, and one constituent of which casing, necessity to be capable to endure all the interior and outside loads. The casing, through its two basic essentials: casing design and casing depth adjustment, are fundamental to a unique wellbore that plays an important role in well integrity. Casing set depths are determined based on fracturing pressure and pore pressure in the well and can usually be obtained from well-specific information. Based on the analyzes using the improved techniques in this study, the following special proposition can be projected: The selection of the first class and materials must be done correctly and accurately in accordance with the depth of casing preparation and the strategy in the considered field that must be taken into account definitely in the drilling and completion period, nevertheless correspondingly in production and upkeep, conversion to an injection well or the opposite, the plug in addition to the closing stage. Features that control the depth of the casing seat have been studied, which consist of fracture gradient, pore pressure with other issues are the surviving lithology’s of rocks. Subsequently defining the casing seat can be sustained with an investigation of the determination of the suitable drilling fluid. According to the consequences of the fracture pressure and pore pressure investigation and the findings of casing setting depth by means of the bottom-up technique, the consequences are gotten to each casing for the 4 studied wells. reference point designed from the rotating table RT. For well A, the conductor casing depth is 47m, the casing surface depth is 533m, the intermediate casing setting depth is 1882 m. Finally, for the production casing depth is 3441 m. Compared to the collapse pressure method, it was found that the bottom-up method gave results that are close and similar to the real results. The results of other wells are included in the search consequences